Promoting Healthy Relationship Development in Teens, Part I: How Dating Smart in Youth Can Foster Better Relationships in Adulthood - Victor William Harris; Gilon Marts; Martie Gillen (EDIS, 2013)
Cultivating healthy dating relationships that can lead to healthy adult romantic and marriage relationships is a science that reflects a complicated calculus of the premarital influences that may shape future relationship stability, quality, and satisfaction. This 4-page fact sheet was written by Victor W. Harris, Gilon Marts, and Martie Gillen, and published by the UF Department of Family Youth and Community Sciences, March 2013.